A Discovery and Characteristics Description of Telosma puberula (Asclepiadoideae) in Mount Gedang Atas and Mount Ijo, Baturagung Mountain Yogyakarta - Widodo Widodo (Biology, Medicine, & Natural Product Chemistry, 2014)
Population of Telosma puberula in community forest bushes was identified at S.07.48'.44.1"; E.110.31.15.8", 411m, Mount Gedang Atas and S 070  04 '04.1"; E 1100  30 '47.9 ", 415m, Mount Ijo. Telosma puberula was also found in Mount Parangan, Mount Mintorogo, Mount Nglanggeran, and Baturagung Mountains Yogyakarta. The identification was based on herbarium specimens collected by Horsfield in 1802 and 1859 from Java island, Indonesia (K000873052, K000873053). Information about Telosma puberula is very limited. This article describe photographs of morphological characters of the plant’s stems, leaves, flowers, and pollinia.